Experimental validation of inventory simulations on molybdenum and its isotopes for fusion applications. (9th September 2020) - Gilbert, M.R.; Packer, L.W.; Stainer, T.
Abstract: Molybdenum is a potential material for future nuclear fusion experiments and power plants. It has good thermo-mechanical properties and can be readily fabricated, making it attractive as an alternative material to tungsten (the current leading candidate) for high neutron flux and high thermal load regions of fusion devices. Unfortunately, exposure to fusion neutrons is predicted to cause significant radioactivity in elemental Mo for decades and centuries after exposure, which would be a problem during maintenance and decommissioning operations. Simulation predictions indicate that Mo activation could be reduced by isotopic adjustment (biasing). If these predictions are proven and validated, and if isotopic adjustment is technically and economically feasible, then Mo could be used in future demonstration and commercial reactors without significantly increasing the amount of long-term, higher-level radioactive waste. Transmutation (inventory) simulations used to predict activation rely on nuclear reaction data. The quality of these data impact on the confidence and uncertainty associated with predictions. Recently, UKAEA has developed benchmarks to test and validate the FISPACT-II inventory code and the input nuclear data libraries. Verification of molybdenum inventory simulations is performed against experimental decay-heat measurements from JAEA's fusion neutron source (FNS) facility and using new data acquired from γ -spectroscopy measurements of Mo irradiated in the ASP 14 MeV facility in the UK. Results demonstrate that FISPACT-II predictions (with TENDL-2019 nuclear data) for Mo are accurate on the short-timescales (minutes, hours of irradiation and minutes, days, weeks of cooling) of these laboratory experiments. However, these kinds of experiments are limited in their coverage of the important radionuclides for decay radiation from Mo on the years, decades and beyond timescales. Further experiments with fusion relevant conditions and timescales, potentially with alternative measurement techniques, are still needed.